2014
DOI: 10.2478/intag-2013-0029
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling and analysis of compressive strength properties of parboiled paddy and milled rice

Abstract: A b s t r a c t. The present investigation deals with analyzing the compressive strength properties of two varieties (Tarom and Fajr) of parboiled paddy and milled rice including: ultimate stress, modulus of elasticity, rupture force and rupture energy. Combined artificial neural network and genetic algorithm were also applied to model these properties. The parboiled samples were prepared with three soaking temperatures (25, 50 and 75°C) and three steaming times (10, 15 and 20 min). The samples were then dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…Differences in the obtained values may result from different grain moistures, loading speeds of the samples and the type of rice used in the tests. The average value of rupture work W Fmax (28.03 mJ) is similar to the values presented, among others, in the work of Nasirahmadi et al [26] (26.9 mJ for Fajr and 28.5 mJ for Tarom) and Sadeghi et al [19] (24.45 mJ for Sazandegi) as well as in the work of Zareiforoush et al [30,31], where the rupture energy assumed values of about 30 mJ. Figures 12-18 summarize the results of mechanical properties of rice grains depending on its volume.…”
Section: The Results Of Testing the Strength Properties Of Rice Grainsupporting
confidence: 89%
“…Differences in the obtained values may result from different grain moistures, loading speeds of the samples and the type of rice used in the tests. The average value of rupture work W Fmax (28.03 mJ) is similar to the values presented, among others, in the work of Nasirahmadi et al [26] (26.9 mJ for Fajr and 28.5 mJ for Tarom) and Sadeghi et al [19] (24.45 mJ for Sazandegi) as well as in the work of Zareiforoush et al [30,31], where the rupture energy assumed values of about 30 mJ. Figures 12-18 summarize the results of mechanical properties of rice grains depending on its volume.…”
Section: The Results Of Testing the Strength Properties Of Rice Grainsupporting
confidence: 89%
“…The hardness of parboiled rice ranged from 128.93 to 216.1 N. The most likely explanation for the increase in hardness during soaking and steaming is that more grains are gelatinized, leading to increased fracture resistance. It has been previously reported that parboiling increases the hardness of rice (Nasirahmadi et al, ), with the effects being accentuated at higher temperatures and longer times.…”
Section: Resuls and Discussionmentioning
confidence: 90%
“…The mechanical properties of seeds were investigated at five moisture contents: 7, 10, 13, 16 and 19 % (optimum moisture content, two lower and two higher). The resistance of individual seeds to mechanical damage was determined in the conditions of quasi-static loads with the use of a Zwick universal testing machine, in accordance with the previously developed methodology (Kuźniar et al, 2013;Nasirahmadi et al, 2014).…”
Section: Methodsmentioning
confidence: 99%